The New Challenges In The Pharmaceutical Industry, What Strategy To Face Them? Sanofi Experience. - Belhamel, Chahrazed (Milev Journal of Research and Studies, 2019)
This research discusses the pharmaceutical industry new challenges, like the slowdown of market growth, showdown of biosimilars and advanced technologies, and tries to highlight the main axes of the facing strategy, by taking the experience of the French company Sanofi as example. Ending by giving some ideas about what could the Algerian pharmaceutical companies get from this experience. As results, there is trending towards biotechnological companies which makes the acquisition or merger with them very important. Second, collaborations are necessary to provide better health solutions. Third, the inevitability of digitalizing the sector and keeping good relationship with investors and society.